Parents’ Knowledge about Type I Diabetes Mellitus at Diabetes and Endocrine Treatment Centers in Baghdad City - faraj, raad (Iraqi National Journal of Nursing Specialties, 2016)
Objectives: The current study aims to evaluate parents’ knowledge towards diabetes mellitus (type I); to identify the association between parents’ knowledge and their demographic characteristics; and to identify the association between parents’ knowledge and demographic characteristics of their children. Methodology: Descriptive study carried out during the period from January to April 2015 on purposive sample of 100 parents with their children with diabetes mellitus who attending diabetes and endocrine treatment center. An evaluation tool is constructed by the researcher based on previous literature regarding aspects of parents’ knowledge toward juvenile diabetes mellitus. Content validity was determined with panel experts. The internal consistency of the instrument was determined through the computation of Alpha Correlation Coefficient, which was statistically acceptable. Data were collected with the assessment tool and the interview technique was used as a means of data collection. The analysis of the data was employed by the use of SPSS version 15.0 through the application of descriptive statistical and inferential statistics such as frequencies, percentages, the mean of scores and chi-square. Results: The findings of the current study show that parents having good knowledge regarding diabetes mellitus (type I). The findings indicate that there is significant association between body mass index and admission to hospital with parents’ knowledge. The findings also show that there is significant association between father’s education and job with parents’ knowledge. Recommendations: The study recommended encouraging parent for more involvement in seminars and educational session on diabetes mellitus (type I) and how to deal with such patient; and further studies are required for focusing on coping strategies to face the burdens of diabetes mellitus (type I) as a chronic health problem.